Close to Real: Large‐Volume 3D Cell Spheroids on a Superamphiphobic Surface. Issue 9 (9th March 2021) - Yu, Yanjia; Dai, Mohan; Xu, Wei; Chen, Shuangshuang; Lu, Qinghua
Abstract: 3D cell spheroids with native cell‐to‐cell junctions and cell‐extracellular matrix interactions can recapitulate the comprehensive physiological environments in vivo, providing new platforms for preclinical drug screening. However, the applications of 3D cell spheroids are limited by the unmatched size, deficient cell abundance, and short service time. In this work, a novel upward culture method on a porous silica superamphiphobic biointerface (SABI) is developed to fully overcome these technical hurdles. Cell suspensions maintain in a state of aquatic marble, accelerating cellular self‐aggregation. Contributing to the upward culture model, this strategy overcomes the shortages of size limitation and media refreshing in the classical methods. Herein, large‐volume 3D cell spheroids with the size of over 1500 µm can be efficiently established within 2 days and subsequently long‐term cultured for more than 20 days. For a close to real biomimetic microenvironment, breast tumor 3D spheroid is applied as a proof of concept, simultaneously employing MCF‐7 cell, cancer‐associated fibroblast (clone 8), and vascular endothelial cell (HUVEC). The large‐volume tumor spheroid with close‐to‐real microenvironment services as a unique paradigm for all‐in‐one biological relevant researches, including the capacity of in situ observation, long‐term incubation, drug screening, and recyclability. Abstract : Superamphiphobic biointerface is applied for the upward culture of large‐volume 3D cell spheroids with close to real microenvironments. This method is efficient and capable of long‐term culture, medium refreshing, in situ analysis, size control, and recyclability.